Organic carbon burial in global lakes and reservoirs - Raquel Mendonça (Nature Portfolio, 2017)
The magnitude of organic carbon burial in lakes and reservoirs is poorly constrained. Here, using a compilation of modern data from the literature and statistical modeling, the authors estimate a global yearly organic carbon burial of 0.15 Pg C in inland waters, of which 40% is stored in reservoirs.